Roughage level and corn processing infinishing diets: subacute acidosis - S.A. Shuey; Robert T. Brandt Jr.; S.M. Gramlich; C.T. Milton (Kansas Agricultural Experiment Station Research Reports, 1994)
Roughage level and method of corn processing were evaluated for the propensity to cause subacute acidosis in a controlled acidosis challenge model. Four ruminally fistulated steers were adapted to a high grain diet, randomly allocated within a 4 x 4 Latin square, and fed a corn-based finishing ration at 2% of BW/day (dry basis) in two equal feedings. Chopped alfalfa hay was used as the roughage source and added at 8% of the diet dry matter or not added. Corn was fed either whole (WSC) or dry rolled (DRC). Roughage level and grain processing had no effect on postchallenge molar percentage of acetate or total volatile fatty acid production. An interaction (P<.05) was seen in both percent propionate and acetate:propionate ratio. Eliminating roughage in the WSC diet resulted in increased production of propionate and a lower acetate:propionate ratio. Ruminal pH at 3 hours postchallenge and intake during the recovery period were lower (P<.05) for 0 vs 8% roughage. Ruminal pH at 3 and 6 hours postchallenge was lower (P<.05) for DRC than for WSC. Intake during the recovery period did not differ between DRC and WSC. Hours below pH 5.6 were greater (P<.05) for DRC vs WSC and for 0 vs 8% roughage. Though statistically higher (P<.05), no biologically significant levels of lactate were found for either DRC or WSC. This study indicates that adding roughage or feeding WSC vs DRC reduces the propensity for subacute acidosis.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704